Elephant–Human Conflict in Bahundangi Region, Jhapa District, Nepal - Shrestha, Ramesh; Koirala, Dilli Prasad (Journal of Natural History Museum, 2015)
This study was conducted for 3½ months from January to mid–April 2013 in the areas of Bahundangi Village Development Committee (VDC) of Jhapa, east Nepal. Although Nepal has the second least number of wild Asian elephants in the world, some of the country’s areas are mostly terrorized by resident and visiting elephant herds from time to time. And, Bahundangi VDC is one of such places where numerous conflicts between wild Asian elephants and human settlements are occurring frequently. The current study was done in order to identify such conflicts like loss of properties and loss of human lives there; and loss of wild elephants so that possible management measures could be developed in order to mitigate dispute for the betterment of both sides.J. Nat. Hist. Mus. Vol. 27, 2013: 59-65